Introducing a Context-Aware Scheme in an intelligent reasoning process - Budán, Paola D. (2016)
Several investigations have been developed around analogies based reasoning in different domains, however the analogy between arguments has not been deeply explored. A semiformal way to express these patterns of reasoning were proposed by Walton, through argument schemes from analogy. From this, it is possible to propose computable approximations for comparing arguments. In this paper we introduce a formalism based on the comparison of arguments through descriptors or labels which describes an aspect that the argument refers to. This formalism allows us classifying similar arguments considering the natural descriptors of them, in a specific context.